RANCANG BANGUN USER INTERFACE DAN USER EXPERIENCE APLIKASI SEMBAKO BERBASIS WEB PADA TOKO G-STAR MENGGUNAKAN METODE HUMAN CENTERED DESIGN - Rumbiak, Rudolf; Afwani, Royana; Irmawati, Budi (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Mataram, 2024)
The advancement of information and communication technology (ICT) has notably impacted various sectors, including trade. For grocery stores, effective User Interface (UI) and User Experience (UX) design are vital to ensure technology is user-friendly across different groups. This research applies the Human-Centered Design (HCD) method to develop the UI and UX for the G-Star grocery store web application, focusing on user needs, preferences, and contexts to create an intuitive interface. The research process includes stages such as user needs analysis, prototype design, usability testing, and iterative design based on feedback. Initially, user needs were identified through interviews and surveys, which guided the creation of application prototypes. These prototypes were then tested for usability, and feedback was used to refine and improve the design. The findings demonstrate that HCD principles enhance UI and UX, leading to higher customer satisfaction and loyalty. Implementing HCD improves user efficiency and convenience, contributing positively to the G-Star grocery store's performance. This research provides valuable insights for technology development in the grocery sector and offers practical guidance for designers and developers, encouraging the use of HCD in similar projects.